Social Inequality in the Digital Economy Era: A Contemporary Sociological Perspective - Samsidar, Samsidar (Socious Journal, 2026)
The rapid development of the digital economy has created new opportunities for economic participation while simultaneously intensifying social inequality across different societal groups. This study aims to analyze the mechanisms and dimensions of social inequality in the digital economy through a contemporary sociological perspective and to propose an inclusive analytical framework. The research employs a qualitative descriptive-analytical approach using a systematic literature review and document analysis of recent scholarly works and policy reports. Data were analyzed through an interactive model consisting of data reduction, data display, and conclusion drawing, supported by triangulation techniques to ensure validity. The findings reveal that digital inequality is driven by multiple interconnected factors, including the digital divide, labor market stratification, platform monopolies, and algorithmic bias. These mechanisms reinforce structural inequalities and create new forms of exclusion, particularly among marginalized groups. The discussion highlights that digital inequality must be understood as a multidimensional phenomenon shaped by technological, economic, and socio-cultural dynamics, requiring integrated and context-sensitive policy responses. In conclusion, addressing social inequality in the digital era requires a comprehensive and inclusive approach that combines equitable access, digital literacy, labor protection, and effective regulation of digital platforms to ensure sustainable and just digital transformation